Adopting the configurational approach to the analysis of job satisfaction in Mongolia - Massoud Moslehpour; Man-Ling Chang; Pham Van Kien; Alaleh Dadvari (European Research on Management and Business Economics (ERMBE), 2022)
Purpose: The purpose of this study is to examine various configurations leading to job satisfaction (JS) in Mongolian private companies through five typical factors: perceived mission statement quality (MSQ), romanticism management philosophy (RMP), psychological ethical climate (PEC), ethical ambiguity (EA), and emotional competence (EC). Method: This study conducts a fuzzy set qualitative comparative analysis (fsQCA) with 202 private sector employees in Mongolia. The current study comes up with three propositions, and the research procedure is divided into two stages. This new approach produces configurations sufficiently, leading to outcomes, equifinality, and conjunction. Findings: This study explores six pathways leading to employee satisfaction. Each pathway consists of the combination of perceived mission statement quality, romanticism management philosophy, psychological ethical climate, low tendency of ethical ambiguity, and managers' emotional competence. Among those, managers' emotional competence is a core condition for high job satisfaction. Implications: Our findings suggest that to satisfy employees, managers' emotional competence plays a vital role in building sufficient conditions that lead to the desired outcomes. Thus, professional development and training are required to maintain and improve managers' competence. Originality/value: This study introduces a fresh theoretical perspective for understanding cause-effect relationships between critical conditions and job satisfaction.
Keywords: J28; J24; J81; 650; Emotional competence; FsQCA; Job satisfaction; Low ethical ambiguity; Mission statement quality; Mongolia; Psychological ethical climate; Romanticism management philosophy